Acid‐sensing ion channels promote the inflammation and migration of cultured rat microglia. Issue 3 (7th November 2014) - Yu, Xiao‐Wei; Hu, Zhuang‐Li; Ni, Ming; Fang, Peng; Zhang, Pei‐Wei; Shu, Qing; Fan, Hua; Zhou, Hai‐Yun; Ni, Lan; Zhu, Ling‐Qiang; Chen, Jian‐Guo; Wang, Fang
<x xml:space="preserve">Abstract</x> Microglia, the major immune cells in central nervous system, act as the surveillance and scavenger of immune defense and inflammatory response. Previous studies suggest that there might be close relationship between acid‐sensing ion channels (ASICs) and inflammation, however, the exact role of ASICs in microglia during inflammation remains elusive. In the present study, we identified the existence of ASICs in the primary cultured rat microglia and explored their functions. By using reverse transcriptase polymerase chain reaction (RT‐PCR), quantitative real‐time PCR (qPCR), western blotting, and immunofluorescence experiments, we demonstrated that ASIC1, ASIC2a, and ASIC3 were existed in cultured and in situ rat microglia. After lipopolysaccharide (LPS) stimulation, the expressions of microglial ASIC1 and ASIC2a were upregulated. Meanwhile, ASIC‐like currents and acid‐induced elevation of intracellular calcium were increased, which could be inhibited by the nonspecific ASICs antagonist amiloride and specific homomeric ASIC1a blocker PcTx1. In addition, both inhibitors reduced the expression of inflammatory cytokines, including inducible nitric oxide synthase and cyclooxygenase 2 stimulated by LPS. Furthermore, we also observed significant increase in the expression of ASIC1 and ASIC2a in scrape‐stimulated microglial migration. Amiloride and PcTx1 prevented the migration by inhibiting ERK phosphorylation. Taken together, these results suggest that ASICs participate in neuroinflammatory response, which will provide a novel therapeutic strategy for controlling the inflammation‐relevant neuronal diseases. GLIA 2015;63:483–496